1986
DOI: 10.1073/pnas.83.12.4533
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant tumor necrosis factor induces procoagulant activity in cultured human vascular endothelium: characterization and comparison with the actions of interleukin 1.

Abstract: Human recombinant tumor necrosis factor (rTNF) was found to act directly on cultured human vascular endothelium to induce a tissue factor-like procoagulant activity (PCA). After a 4-hr incubation in rTNF (100 units/ml), serially passaged endothelial cells isolated from umbilical veins, saphenous veins, iliac arteries, and thoracic aortae demonstrated a dramatic increase (4-to 15-fold, 21 experiments) in total cellular PCA as measured with a one-stage clotting assay. rTNF-induced PCA was also expressed at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
391
3
8

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 982 publications
(421 citation statements)
references
References 40 publications
19
391
3
8
Order By: Relevance
“…LPS-induced expression of TF (CD142) in activated monocytes triggers thrombosis and may culminate in disseminated intravascular coagulation (DIC) [12]. Moreover, TNF-a per se is known to be a potent inducer of TF expression [13]. The occurrence of DIC as a secondary complication of sepsis with gram-negative bacteria is associated with poor prognosis and is an independent predictor of mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…LPS-induced expression of TF (CD142) in activated monocytes triggers thrombosis and may culminate in disseminated intravascular coagulation (DIC) [12]. Moreover, TNF-a per se is known to be a potent inducer of TF expression [13]. The occurrence of DIC as a secondary complication of sepsis with gram-negative bacteria is associated with poor prognosis and is an independent predictor of mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory mechanisms upregulate procoagulant factors, downregulate natural anticoagulants and inhibit fibrinolytic activity [2]. Endotoxin, tumor necrosis factor alpha (TNF-a) and interleukin-1a induce tissue factor (TF) expression, primarily on endothelial cells and monocytes/macrophages, promoting blood coagulation [3]. Activation of the complement C5b-C9 complex changes the cell surface to a more procoagulant phenotype by the shift of negatively charged phospholipids from the inner to the outer membrane [4].…”
Section: Introductionmentioning
confidence: 99%
“…TNF is an endogenous pyrogen [9], and TNF shares with IL-1 many biologic functions. Recombinant IL-1 and TNF increase hepatic acute-phase protein synthesis [10], decrease hepatic albumin synthesis [10,11], in duce synovial collagenase and prostaglandin E2 [12], cause release of procoagulant activity from vascu lar endothelium [13], and inhibit lipoprotein lipase synthesis [14,15]. We recently demonstrated that in jection of recombinant human IL-1 (3 or recombinant human TNF decreases systemic arterial pressure in the rabbit and that combined administration of IL-1 and TNF is more potent than either cytokine alone in induction of a shock-like state [16].…”
mentioning
confidence: 99%